Effect of partial substitution of sodium with potassium chloride in the fermenting brine on organoleptic characteristics and bioactive molecules occurrence in table olives debittered using Spanish and Castelvetrano methods. (29th December 2016) - Ambra, Roberto; Lucchetti, Sabrina; Moneta, Elisabetta; Peparaio, Marina; Nardo, Nicoletta; Baiamonte, Irene; Di Costanzo, Maria Gabriella; Saggia Civitelli, Eleonora; Pastore, Gianni
Summary: This research was aimed at testing whether the partial substitution of NaCl with KCl (50 or 75% relative substitution) in the fermenting brine of green table Nocellara del Belice olives debittered using two used method (Spanish and Castelvetrano) affected the presence of nutritionally relevant molecules (tocopherols, carotenoids, squalene, phenolic compounds) or the organoleptic characteristics of the table‐ready product. Results support the effectiveness of NaCl partial substitution by potassium chloride for olive processing, with the advantage of a significant decrease in the amount of sodium in the end product. The presence of the main bioactive molecules remained substantially unchanged, but KCl was associated with an increase in bitterness in both debittering methods. However, bitter properties (bitter, persistence and aftertaste) of olives obtained through the modification of Castelvetrano method still remained below those debittered with the classic Spanish method preserving, for such olives, the characteristic of 'sweet olives'. Abstract : Nocellara del Belice olives were debittered using Spanish and Castelvetrano methods in presence of different NaCl/KCl ratios. Bioactive molecules and organoleptic characteristics were assayed respectively by means of HPLC and sensory analysis.